2021
DOI: 10.1139/cjfas-2020-0242
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning maternal and exogenous diet contributions to otolith 87Sr/86Sr in kokanee salmon (Oncorhynchus nerka)

Abstract: Strontium isotopes (87Sr/86Sr) recorded in the otoliths of Pacific Salmon (Oncorhynchus spp.) are commonly used to identify natal origin. For species that migrate at or soon after emergence, the embryonic region of the otolith provides the only record of provenance. However, maternal contribution of Sr from the yolk can confound the isotopic signature of the natal site. We experimentally quantified maternal and exogenous diet contributions to otolith 87Sr/86Sr over embryonic development in Kokanee salmon (O. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
2
11
1
Order By: Relevance
“…In contrast, Hegg et al (2018) reported the shift occurred later, approximately 225 μm, with respect to otolith elemental signatures (i.e., Mn/Ca, Ba/Ca and Sr/Ca), and thus suggested that this transition represented an ontological change within the developing fish separate from hatching and possibly related to fish emergence. Interestingly, work on a related salmonid ( Oncorhynchus nerka ) by Janak et al (2021) reported shifts in otolith 87 Sr/ 86 Sr and Sr/Ca associated with hatching and yolk sac absorption that occurred at an average otolith radius of 67 and 118 μm, respectively, which was comparable to this study.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In contrast, Hegg et al (2018) reported the shift occurred later, approximately 225 μm, with respect to otolith elemental signatures (i.e., Mn/Ca, Ba/Ca and Sr/Ca), and thus suggested that this transition represented an ontological change within the developing fish separate from hatching and possibly related to fish emergence. Interestingly, work on a related salmonid ( Oncorhynchus nerka ) by Janak et al (2021) reported shifts in otolith 87 Sr/ 86 Sr and Sr/Ca associated with hatching and yolk sac absorption that occurred at an average otolith radius of 67 and 118 μm, respectively, which was comparable to this study.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, work on a related salmonid (Oncorhynchus nerka) by Janak et al (2021) reported shifts in otolith 87 Sr/ 86 Sr and Sr/Ca associated with hatching and yolk sac absorption that occurred at an average otolith radius of 67 and 118 μm, respectively, which was comparable to this study.…”
Section: Environmentally Derived 87 Sr/ 86 Sr and Sr/casupporting
confidence: 87%
See 3 more Smart Citations